Resonant method for the measurement of quality of laminated cores - Schneider, Michael; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
Measurement of the electromagnetic properties of soft magnetic materials becomes increasingly important with the demand for more efficiency in electric machines. In addition to the B-H characteristic and the permeability, which is necessary in a FEM program for the calculation of electromagnetic fields for realistic simulation of an electrical machine, today's measurement methods obtain additional information on the quality of finished metal package. Thus, it is possible to identify the engine iron losses, divided into hysteresis and eddy current losses. But under the current state of the art, only samples are provided for checking the quality of laminated cores according to the process steps sheet metal cutting, stacking and packing. For this, several stators are taken from current production and loss measurement is performed. For the measurement of the core loss (toroidal or stator geometry) are each wound a primary and a secondary winding on a sample. The wrapping is done by hand and is therefore very time-consuming. An inline measurement of all stators from a production line is not possible with this effort. To increase the quality and safety of the transparency of the manufactured products a 100% inspection is interesting. In terms of process control of the whole production line a 100% measurement strategy provides the framework for a comprehensive analysis for refining the appropriate feedback variables (tool change times, machine parameters, etc.). The losses should be recorded with the new measurement method during manufacturing and provided to the parent manufacturing control system as information. Thus machine parameters can be adjusted directly or tools are detected at the limit of wear and can be rapidly replaced to ensure a consistently high quality of sheet metal packages. A new method of quality assurance for laminated cores will be presented in this paper.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cutting; iron losses; measurement method; sheet metal; stacking